Absentee Landlordism and Municipal Government in Nineteenth Century St. John's - Baker, Melvin (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1986)
This paper examines the influence of the leasehold system of land tenure on the structure of municipal government in 19th century St. Johns. This influence can be seen in the shaping of St. John's streets and physical growth, regulations governing building, property assessments levied to pay for local services, and even in the formation of municipal institutions themselves. It was also evident in the failures of the Newfoundland legislature and the St. John's Municipal Council to successfully tax the annual ground rents the predominantly British absentee landlords received from leasing their land in St. John's.These efforts to assess the ground rents of the absentees were motivated by the desire of local tenants to make them pay their share of municipal taxation. There was naturally bitter resentment in St. John's against the absentee landlords and their agents. Tenants were also angered by the value of land in the town which was constantly being raised without contribution from the absentees. This situation was of considerable significance in the development of St. John's, for the system of land tenure not only discouraged the imposition of property taxes but also worked against the establishment of municipal government. Consequently, St. John's municipal government in the 19th century differed from the more traditional route of local government that was followed, for instance, by Canadian cities such as Halifax or Toronto. In St. John's the Municipal Council, established in 1888, had control of the water supply, streets, sewers, parks, the fire brigade, and building regulations only, while the Newfoundland legislature retained responsibility over the city's other institutions and services. The history of the Municipal Council after 1888 was one of limited self-rule, characterized by inadequate administrative, legislative power, political interference from the government, and insufficient revenue.